INTERNATIONAL - LEGAL ASPECTS OF COURT PROTECTION ENVIRONMENTAL RIGHTS OF CITIZENS - Поліщук, Інна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to analyze and summarize the basic mechanisms, means and guarantees for the implementation of environmental protection of citizens, in accordance with the Aarhus Convention and international case law. Provide an assessment of the activities of specialized environmental courts established in different countries and their enforcement practices for the protection of citizens' environmental rights. Support and justify the need to establish such courts in other countries, and in particular in Ukraine, in the context of reforming the national judicial system and globalization of environmental issues. Research methods: used and analyzed scientific approaches of some domestic and foreign scientists on certain issues of international legal protection of environmental rights of citizens in court, as well as provisions of the Aarhus Convention, which are decisive in regulating such protection. Results: the need to improve the international and national environmental policies of states, to develop clearer and simpler mechanisms for realizing the protection of environmental rights of citizens, to establish and enhance the role of specialized environmental courts, which should contribute to improving the efficiency of justice in the area of citizens' implementation of environmental rights. Discussion: in recent years, research into the environmental rights of citizens and the problems of their protection have occupied one of the leading positions in the scientific concept of environmental law of Ukraine and other countries. Updating of the research is caused by changes in international environmental policy and international environmental legislation; the desire of the international community for a high degree of environmental protection, improving its quality, improving the standard and quality of life of people; the need to identify and seek mechanisms to implement the protection of citizens' environmental rights, including through the courts. Problems of judicial protection of environmental rights of citizens are related to the lack of certain environmental terms in the legislation of some countries and their content, the need to independently prove the facts of violation of environmental rights by citizens and the causal link between the act and the consequences that have occurred, as well as in a number of countries specialized environmental courts, specially trained judges and court experts and, accordingly, simplified court procedures for the implementation of environmental protection mechanisms citizens, because courts of general jurisdiction are not always capable of effectively administering justice in this area. The practice of environmental courts of different countries and the European Court of Human Rights shows that the successful organization and enhancement of the role of the specialized environmental court contributes to the efficiency of justice in the implementation, protection and restoration of violated environmental rights of citizens.